The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s11136-018-1789-4
|View full text |Cite
|
Sign up to set email alerts
|

Children on dialysis as well as renal transplanted children report severely impaired health-related quality of life

Abstract: ObjectivesTo assess health-related quality of life (HRQoL) across three renal replacement therapy modalities (preemptive transplant, non-preemptive transplant, and dialysis) in comparison with the healthy norm and other chronic health conditions, and to explore related patient factors.Study designAll prevalent end-stage renal disease (ESRD) patients aged 8–18 years who spent at least 6 months on their current treatment modality in the Netherlands, Belgium, and part of Germany were approached to complete the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
4
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 30 publications
(32 reference statements)
5
53
4
6
Order By: Relevance
“…Our findings support a previous report suggesting adaptation to kidney transplant may take up to12 months, but differ from previous cross‐sectional studies, which did not find significant differences in total HRQoL scores between dialysis and transplant groups . This may be explained in part by higher post‐transplant scores among our cohort.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our findings support a previous report suggesting adaptation to kidney transplant may take up to12 months, but differ from previous cross‐sectional studies, which did not find significant differences in total HRQoL scores between dialysis and transplant groups . This may be explained in part by higher post‐transplant scores among our cohort.…”
Section: Discussionsupporting
confidence: 63%
“… These findings are consistent with the findings of Olausson et al who found most pediatric transplant recipients were of the opinion that they lived a normal life. Splinter et al found lower HRQoL scores among transplant recipients who received transplant >1 year ago, suggesting recipient HRQoL may fall after the first year. Our findings of clinically significant improvement in recipient Worry subscale score contrasts with the qualitative findings reported by Tong et al who found continued significant barriers related to fear and uncertainty over the future among adolescent recipients following kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future prospects regarding schooling and further education are poor if they are in need of dialysis—which is time consuming and often produces side effects. Significantly reduced quality of life is found among children with ESKD (Francis et al ), and in health‐related quality of life at all stages of chronic kidney disease (CKD) (Moreira et al ; Splinter et al ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Children with ESKD need renal replacement therapy or transplantation to survive, and their death rate remains 30-fold higher than for healthy children (Chong et al, 2017;McDonald & Craig, 2004). Thus, children with ESKD face lifelong increases in morbidity and mortality, together with reduced quality of life (Francis et al, 2019) and health-related quality of life (Moreira, Bouissou Morais Soares, Teixeira, Simões e Silva, & Kummer, 2015;Splinter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%